A Rare complication of Cholelithiasis: Cholecystocolic Fistula – Case Report - Shrestha, Anup; Bhattarai, Abhishek; Gurung, Kesh Maya; Chand, Manoj (Med Phoenix, 2021)
Although the pre-operative diagnosis of the cholecystocolic fistula has been reported, yet it is by no means a common finding. Cholecystocolic fistula is the second most type of biliary enteric fistula after cholecystoduodenal fistula. Cholecystogastric fistula is least commonly reported. We report our experience with cholecystocolic fistula discovered on imaging which was subsequently confirmed through surgery. The standard treatment for CCF is open cholecystectomy and closure of the fistula. Failure to identify preoperatively or intra-operatively can lead to various complications.